Covid-19: Perspectives on Innate Immune Evasion - Taefehshokr, Nima; Taefehshokr, Sina; Hemmat, Nima; Heit, Bryan (Frontiers in Immunology, 2020)
The ongoing outbreak of COVID-19 infection achieved pandemic status on 11th March 2020. As of 8th September 2020 it has caused over 890,000 mortalities world-wide. Coronaviral infections are enabled by potent immunoevasory mechanisms that target multiple aspects of innate immunity, with SARS-CoV-2 able to induce a cytokine storm, impair interferon responses, and suppress antigen presentation on both MHC class I and class II. Understanding the immune responses to SARS-CoV-2 and its immunoevasion approaches will improve our understanding of pathogenesis, virus clearance, and contribute towards vaccine and immunotherepeutic design and evaluation. This review discusses the known host innate immune response and immune evasion mechanisms driving SARS-CoV-2 infection and pathophysiology.